Policy-driven democratization : geometrical perspectives on transparency, accountability, and corruption - Blind, Peride K.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Policy-Driven Democratization offers a comprehensive conceptual analysis of each one of these fuzzy terms separately to then sew them together in one complete and coherent package of democratization.
Keywords: Science; Science; Science, general